The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1016/j.fct.2003.08.021
|View full text |Cite
|
Sign up to set email alerts
|

The FEMA GRAS assessment of cinnamyl derivatives used as flavor ingredients

Abstract: This publication is the seventh in a series of safety evaluations performed by the Expert Panel of the Flavor and Extract Manufacturers Association (FEMA). In 1993, the Panel initiated a comprehensive program to re-evaluate the safety of more than 1700 GRAS flavoring substances under conditions of intended use. Elements that are fundamental to the safety evaluation of flavor ingredients include exposure, structural analogy, metabolism, pharmacokinetics and toxicology. Flavor ingredients are evaluated individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 91 publications
1
71
0
Order By: Relevance
“…Human exposure to t-CA is common due to its presence in the diet, fragrances, electronic cigarettes, and use as a complementary treatment of diabetes and other maladies (Friedman et al, 2000;Adams et al, 2004;Bickers et al, 2005;Crawford, 2009). From a toxicological perspective, it contains a well known structural alert (i.e., a,b-unsaturated carbonyl), reacts with skin proteins (Elahi et al, 2004), and is implicated in contact dermatitis (Seite-Bellezza et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Human exposure to t-CA is common due to its presence in the diet, fragrances, electronic cigarettes, and use as a complementary treatment of diabetes and other maladies (Friedman et al, 2000;Adams et al, 2004;Bickers et al, 2005;Crawford, 2009). From a toxicological perspective, it contains a well known structural alert (i.e., a,b-unsaturated carbonyl), reacts with skin proteins (Elahi et al, 2004), and is implicated in contact dermatitis (Seite-Bellezza et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…It is a generally recognized as safe (GRAS) molecule approved for use in foods by the Food and Drug Administration (FDA). The U. S. Flavoring Extract Manufacturers' Association reported that TC has a wide margin of safety between conservative estimates of intake and no observed adverse effect levels, from sub-chronic and chronic studies (Adams et al, 2004). The report also indicated no genotoxic or mutagenic effects due to TC.…”
Section: Trans-cinnamaldehydementioning
confidence: 78%
“…Trans-cinnamaldehyde (TC) is a major component of the bark extract of cinnamon (Adams et al, 2004). It is a generally recognized as safe (GRAS) molecule approved for use in foods by the Food and Drug Administration (FDA).…”
Section: Trans-cinnamaldehydementioning
confidence: 99%
“…Additionally, transcinnamaldehyde has been shown to reduce the expression of several virulence genes essential for Uropathogenic Escherichia coli (UPEC) motility, host cell attachment and invasion. trans-Cinnamaldehyde has been recognized by the FDA as a safe molecule for use in food, and sub-chronic and chronic studies show this compound to have no adverse effects (Adams et al, 2004). These findings suggest that both transcinnamaldehyde and curcumin are potential candidates for the inhibition of biofilm production, as well as anti-adhesive agents (Amalaradjou et al, 2011).…”
Section: Introductionmentioning
confidence: 75%